Ideology and Empire in Eighteenth-Century India The British in Bengal - Travers, Robert (Cambridge University Press, 2013)
Edmund Burke’s pregnant pause invited the commons of Great Britain to gaze on the lonely, impoverished emperor of Hindustan, and to beware the fate of empires. Seven years after the publication of the first volume of Edward Gibbon’s Decline and Fall of the Roman Empire, imperial history appeared to Burke as the record of ‘awful lessons’. Britain’s own imperial destiny hung in the balance.